Classification of precipitation anomalies in the Rio Grande do Sul in ENSO events in the 20th century - Valente, Pedro Teixeira; Viana, Denilson Ribeiro; Aquino, Francisco Eliseu; Simões, Jefferson Cardia (Sociedade & Natureza, 2023)
This study investigated the intensity and spatial distribution of precipitation anomalies in Rio Grande do Sul state (RS) during the 20th century by analyzing the influence of El Niño – Southern Oscillation (ENSO) in its three phases. Reanalyzes from the University of Delaware (V5) were used. Precipitation anomalies were divided into three zones (Campaign, Plateau, Coast) to investigate possible differences in precipitation under ENSO influence. Alexandersson's Standard Normal Homogeneity Test was applied to verify possible structural breaks. Wavelets were used to rate the periodicity of precipitation anomalies into three phases. Anomalies that occurred in El Niño and La Niña phases were classified in contingency tables as weak, average, and strong to evaluate the qualitative behavior of these precipitation anomalies. It was found that precipitation anomalies presented a structural break in 1955 when the tendency to positive anomalies increased. From 1955, precipitation anomalies increased at least 0.5 standard deviation while the frequency of these anomalies decreased from 85 to 60 months. Peaks of positive anomalies in El Niño were higher than 200 mm. In neutral cases, anomalies intensified in 0.5 standard deviation since 1970. Negative anomalies did not show specific behavior in any ENSO phase. Contingency tables indicated that La Niña events did not present any visible influence pattern. It could intensify the episodes of positive and negative precipitation anomalies in at least 0.5 (-0.5) standard deviation. Therefore, La Niña events could increase or decrease the monthly anomaly but do not show any tendency to negative anomalies. Weak El Niños tends to contribute to negative precipitation anomalies while strong cases are associated with an average increase of 2 standard deviations in positive anomalies. It was concluded that the influence of ENSO in RS is stronger in El Niño than in La Niña. Still, both may induce negative and positive anomalies, depending on the intensity of each case. Wavelet analysis revealed that cycles that did not coincide with El Niño/La Niña showed an increase (decrease) of 0.5 (-0.5) standard deviation is positive (negative) anomalies. The increase of anomalies in neutral phases indicated that other climatic variability modes and the intensity of meteorological events decreased the 25 and 43 months cycles and increased the precipitation in RS.